A hybrid power system based on fuel cell, photovoltaic source and supercapacitor - Seydali Ferahtia (SN Applied Sciences, 2020)
Abstract In this study, we present an ameliorated power management method for dc microgrid. The importance of exploiting renewable energy has long been a controversial topic, and due to the advantages of DC over the AC type, a typical DC islanded micro-grid has been proposed in this paper. This typical microgrid is composed of two sources: fuel cell (FC), solar cell (PV) and one storage element [supercapacitor (SC)]. Here, we aimed to provide a management strategy that guarantees optimized bus voltage with arranged power-sharing between the sources. This proposed management aims to provide high-quality energy to the load under different loading conditions with variable solar irradiance, taking into account the FC state. Due to the slow dynamics of the FC, the SC was equipped to supply the transient period. A management algorithm is implemented to hold the DC bus voltage stable against the load variations. The management controller is based on differential flatness approach to generate the references. The DC bus is regulated by the SC energy; to reduce the fluctuations in the DC bus voltage, The PI controller is implemented. This proposed strategy reduces the voltage ripple in the DC bus. Moreover, it provides permanent supplying to the load with smooth behaviour over the sudden changes in the demand as depicted in the simulation results. Our study revealed that this proposed manager can be used for this kind of grids easily.